Lipid storage myopathy due to late-onset multiple Acyl-CoA dehydrogenase deficiency with novel mutations in ETFDH: A case report - Tian, Huihong; Zhong, Yi; Liu, Zhihua; Wei, Liping; Yuan, Yanbo; Zhang, Yuhu; Wang, Limin (Frontiers in Neurology, 2022)
Background Lipid storage myopathy (LSM) is an autosomal recessive inherited lipid and amino metabolic disorder with great clinical heterogeneity. Variations in the electron transfer flavoprotein dehydrogenase (ETFDH) gene cause multiple acyl-CoA dehydrogenase deficiency (MADD), and have a manifestation of LSM. Muscle biopsy helps clarify the diagnosis of LSM, and next-generation sequencing (NGS) can be useful in identifying genomic mutation sites. The diagnosis of MADD contributes to targeted therapy. Case presentation We report on a teenager who appeared to have muscle weakness and exercise intolerance at the onset. Before the referral to our hospital, he was unsuccessfully treated with glucocorticoid for suspected polymyositis. The next-generation sequencing of the proband and his parents revealed heterozygous variations, c.365G>A (p.G122D) inherited from the father, c.176-194_176-193del, and c.832-316C>T inherited from the mother in the ETFDH gene. The tandem mass spectrometry identified the mutations to be pathogenic. However, his parents and his younger sister who were detected with a mutation of c.365G>A presented no clinical symptoms. This indicates that the combination of the three compound heterozygous mutations in ETFDH is significant. After MADD was diagnosed, a dramatic clinical recovery and biochemical improvement presented as riboflavin was given to the patient across a week, which further confirmed the diagnosis of MADD. Conclusion Our observations extend the spectrum of ETFDH variants in Chinese the population and reinforce the role of NGS in diagnosis of MADD. Early diagnosis and appropriate treatment of LSM lead to great clinical efficacy and avoid some lethal complications.